Răspuns :
A= 16√3−12√3+21√3−16√3+15√3 = 24√3
B= 36√2 −27√2+24√2−21√2−6√2= 6√2
C= 15√6−16√6+15√6−12√6−16√6=
C = 30√6− 44√6 = (−14√6 )
A×c /b= 24√3 × (-14√6) / 6√2 = Simplificăm cu 6
= 4√3×−14√6/√2 =
= −56√18/√2 = − 56√9 = −56×3=(-168)
B×C/A= 6√2×−14√6 / 24√3 = Simplificăm cu 6
= √2×−14√6/4√3 = Simplificăm cu 2
= √2×−7√6/2√3 =
= −7√12/2√3= Simplificăm cu √3
= −7√4 /2 =
−7×2/2= Simplificăm cu 2
= −7
B= 36√2 −27√2+24√2−21√2−6√2= 6√2
C= 15√6−16√6+15√6−12√6−16√6=
C = 30√6− 44√6 = (−14√6 )
A×c /b= 24√3 × (-14√6) / 6√2 = Simplificăm cu 6
= 4√3×−14√6/√2 =
= −56√18/√2 = − 56√9 = −56×3=(-168)
B×C/A= 6√2×−14√6 / 24√3 = Simplificăm cu 6
= √2×−14√6/4√3 = Simplificăm cu 2
= √2×−7√6/2√3 =
= −7√12/2√3= Simplificăm cu √3
= −7√4 /2 =
−7×2/2= Simplificăm cu 2
= −7